INOVASI PELAYANAN HUKUM OLEH JAKSA PENGACARA NEGARA PADA KEJAKSAAN NEGERI PADANG DENGAN MEMBUAT POJOK LAYANAN DIKANTOR STAKEHOLDER - Vivi Nilasari; Aldri Frinaldi (Ensiklopedia of Journal, 2026)
Legal services are one of the strategic functions of the State Attorney/Prosecutor (Jaksa Pengacara Negara - JPN) in supporting good governance and encouraging the creation of legal certainty for government agencies and the public. This study discusses the implementation of legal service innovation by the State Attorney/Prosecutor at the Padang District Attorney's Office (Kejaksaan Negeri Padang) through the establishment of JPN Service Corners (Pojok Layanan JPN) in stakeholder offices such as regional government agencies, Regionally Owned Enterprises (Badan Usaha Milik Daerah - BUMD), and other government institutions. The main objective of this innovation is to bring access to legal consultation services, legal aid, and legal opinions closer to the parties who need them, while simultaneously enhancing the effectiveness of cross-sectoral coordination. Overall, the establishment of JPN Service Corners in stakeholder offices can serve as a model of best practice for the Prosecutor's Office in expanding the reach of preventive and repressive legal services, as well as strengthening the role of the Prosecutor's Office as the government's legal advisor. The recommendation of this study is the need for strengthening internal regulations, increasing the capacity of JPN, and expanding the scope of the service corners to other institutions in order to support clean and effective governance.Keywords: State Attorney, Legal Services, Public Service Innovation, JPN Service Corner, Good Governance